Lecture 7 Notes

# Ie cos2asin2a 1 applications vibrations 37

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: cos(A) sin(B ) cos(A + B ) = cos(A) cos(B ) − sin(A) sin(B ) 2 cos(3t + π /3) = 2 cos(π /3) cos(3t) − 2 sin(π /3) sin(3t) = cos(3t) − √ 3 sin(3t) Applications - vibrations (3.7) • Converting from sum-of-sin-cos to a single cos expression: • Example: 4 cos(2t) + 3 sin(2t) cos(A − B ) = cos(A) cos(B ) + sin(A) sin(B ) Applications - vibrations (3.7) • Converting from sum-of-sin-cos to a single cos expression: • Example: 4 cos(2t) + 3 sin(2t) 4 3 cos(A − B ) = cos(A) cos(B ) + sin(A) sin(B ) Applications - vibrations (3.7) • Converting from sum-of-sin-cos to a single cos expression: • Example: 4 cos(2t) + 3 sin(2t) 4 3 cos(A − B ) = cos(A) cos(B ) + sin(A) sin(B ) (cos(A), sin(A)) must lie on the unit circle. i.e. cos2(A)+sin2(A) = 1. Applications - vibrations (3.7) • Converting from sum-of-sin-cos to a single cos expression: • Example: 4 cos(2t) + 3 sin(2t) ￿ ￿ 4 3 =5 cos(2t) + sin(2t) 5 5 4 3 cos(A − B ) = cos(A) cos(B ) + sin(A) sin(B ) (cos(A), sin(A)) must lie on t...
View Full Document

Ask a homework question - tutors are online